Grain Quality Engineering for Organic Metal Halide Perovskites Using Mixed Antisolvent Spraying Treatment. Issue 1 (7th January 2020) - Lee, Da Seul; Bing, Jueming; Kim, Jincheol; Green, Martin A.; Huang, Shujuan; Ho-Baillie, Anita W. Y.
Abstract : Anti‐Solvent Treatments In article number 1900397, Anita W. Y. Ho‐Baillie and co‐workers report a mixed anti‐solvent treatment by spraying acetonitrile‐added chlorobenzene for the fabrication of high‐quality perovskite films. Although the lower boiling point of acetonitrile preserves the morphology of the perovskite film, it has a significant impact on perovskite crystallization dynamics. Moreover, the method developed is scalable for future large‐area devices.